Rationalism and Future Political Islam in Indonesia - Nurus Shalihin (Jurnal Studi Pemerintahan, 2013)
This paper aims to examine the Muslim rationality in legislative and executive election, and also to understand the reason why they choose national party, or Islamic party based on the alkali data of legislative and executive election in West Sumatera from 2004-2009 periods. The paradigm of research is a rational choice theory. This paradigm helps to understand the political behavior of Muslim in West Sumatera in legislative and executive election of 2004-2009 period. Finally, the research finds out that Muslim in West Sumatera always make a political choice rationale, and ignore the primordial consideration to choose the party. This fact is crucial factor why the Islamic party was lost in West Sumatera, and other places in Indonesia.